REVIEWS - Brosius, Maria (Journal of Semitic studies, 2003)
A Survey of Neo-Elamite History (State Archives of Assyria Studies Volume XII) Matthew W. Waters . Neo-Assyrian Text Corpus Project, Helsinki 2000. Pp. xviii + 139. Price: $29.50 . ISBN: 951-45-9044-9.